Revisi Kebijakan Pengangkatan PLT Kepala Daerah - Angga Rosidin; Iip Mualip; A'rif Rokhman; Leo Agustino; Rina Yulianti (Syntax Corporation, 2023)
The purpose of this investigation and analysis is to produce a plan for how to elect temporary regional heads in perfect local government. The termination of the 2022 regional elections is a consequence of the 2024 simultaneous regional elections. The Indonesian government will then appoint dozens of regional governors to serve as interim leaders until a permanent replacement is found. In terms of the problem framework, this study asks,